Corrosion inhibition of mild steel by methyl violet and bromide ion in sulfuric acid solution. Issue 6 (27th May 2014) - Wang, L.; Zhang, S.‐W.; Guo, Q.; Zheng, H.; Lu, D.‐M.; Peng, L.; Xion, J.
<x xml:space="preserve">Abstract</x> The corrosion inhibition behavior of methyl violet in the absence and presence of bromide ion on mild steel in sulfuric acid solution has been studied by weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy. The results indicate that the corrosion of mild steel is obviously reduced by methyl violet in combination with bromide ion. Electrochemical studies show that methyl violet and bromide ion act as mixed type inhibitors retarding the cathodic and anodic corrosion reactions with emphasis on the former and do not change the mechanism of either hydrogen evolution reaction or mild steel dissolution. The corrosion reaction is controlled by charge‐transfer process. The adsorption of the inhibitors on the mild steel surface obeys the Langmuir adsorption isotherm model. The calculated thermodynamic and kinetic parameters (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjqkbf448" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔGadso</alternatives>, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjqkbf43r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔHadso</alternatives>, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjqkbf469" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔSadso</alternatives>, Kads, and Ea) reveal a strong interaction between inhibitors and mild steel surface. The values of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjqkbf45s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔGadso</alternatives> show that the inhibitors are adsorbed on the mild steel surface in sulfuric acid by chemical adsorption mechanism.